Inappropriate Defibrillator Shocks due to Mechanical Inference from an Investigational Device - Ying chi Yang; Thein Tun Aung; Abdul Wase (Case Reports in Cardiology)
Cardiac contractility modulation (CCM) is an investigational device-based therapy to enhance ventricular contractility in systolic heart failure patients who are not candidates for cardiac resynchronization therapy (CRT) owing to the absence of wide QRS complexes or who have failed to respond on CRT. The principal mechanism is based on the stimulation of cardiac muscles by nonexcitatory electrical signals to augment the influx of calcium ions into the cardiomyocytes. The majority of patients receiving CCM therapy have concurrent implantable cardioverter defibrillators, and the manufacturer declares both devices can be used in parallel without any interactions. Nevertheless, proper lead positioning of both devices are crucial, and it is mandatory to check device-device interactions during each and every cardiac electronic implantable device-related procedure to prevent adverse outcomes.